Hyperspectral abdominal laparoscopy with real-time quantitative tissue oxygenation imaging: a live porcine study - Oscar MacCormac; Oscar MacCormac; Conor C. Horgan; Conor C. Horgan; Dale Waterhouse; Dale Waterhouse; Philip Noonan; Philip Noonan; Mirek Janatka; Mirek Janatka; Richard Miles; Richard Miles; et al. (Frontiers in Medical Technology)
BackgroundIschaemia is a critical complication, and can result in poor surgical outcomes. While intra-operative overt ischaemia can be perceived with the naked eye, timely recognition of borderline perfusion can prevent post-operative ischaemic complications, which is particularly relevant for colorectal anastomoses. Consequently, there is a clinical need for new technologies to intra-operatively assess tissue oxygenation (indicative of end organ perfusion), with minimal disruption to the surgical workflow. Here we present a hyperspectral imaging (HSI) system for laparoscopic surgery. This system provides live, easy to interpret, tissue oxygenation (StO2) maps with associated quantitative values.MethodsWhite light view and tissue oxygenation maps were reconstructed from a protoype laparoscopic Hyperspectral Surgical System (HSS). First, in a live porcine model (55 kg female), the mesentery of a small bowel loop was temporarily occluded with a laparoscopic grasper, then released whilst being imaged with HSI. The quantitative StO2 values obtained from the HSS were compared with those of a non-invasive tissue oximetry probe (Moor VMS-Oxy, Moor Instruments Ltd, United Kingdom). Secondly, mimicking a laparoscopic colon resection and anastomosis, the colorectal junction was mobilised laparoscopically, exteriorised, transected, anastomosed and repositioned in the abdominal cavity. In order to compare healthy and ischaemic colon, the distal part was intentionally devascularised. Tissue oxygenation maps were compared with indocyanine green fluorescence angiography (ICG-FA) of the anastomotic region.ResultsThe HSS was used as the primary scope to complete a laparoscopic colorectal anastomosis, providing a simultaneous white light view and hyperspectral information. Quantitative results from small bowel imaging were shown to correlate with measurements from the superficial tissue oximetry probe. Real-time tissue oxygenation maps were shown to visually correlate with ICG-FA.ConclusionThe HSS can guide laparoscopic surgical procedures whilst providing visual and quantitative tissue oxygenation information in a live animal model. This paves the way for further studies to assess clinical applications.